2020
DOI: 10.1097/gox.0000000000003029
|View full text |Cite
|
Sign up to set email alerts
|

Panniculectomy: Practical Pearls and Pitfalls

Abstract: Summary: Panniculectomy is an increasingly common operation, given the current obesity epidemic and the increasing prevalence of bariatric surgery. At first glance, it could be considered a technically simple operation; however, this procedure can be fraught with complications, given the patient population and high demands placed on compromised abdominal tissue. Sufficient attention must be given to the nuances of patient optimization and surgical planning to maximize safe and ideal outcomes. We hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Other effective techniques for panniculectomy with a mechanical lift have been described, including K-wires, the orthopedic trapeze, and Steinmann pins. 11 Our setup utilized towel hooks, which are safe for the patient as they do not deeply penetrate the abdominal wall. The use of multiple hooks to distribute the weight of the pannus also reduced pressure and prevented tearing of the skin that can occur when using Steinman pins.…”
Section: Discussionmentioning
confidence: 99%
“…Other effective techniques for panniculectomy with a mechanical lift have been described, including K-wires, the orthopedic trapeze, and Steinmann pins. 11 Our setup utilized towel hooks, which are safe for the patient as they do not deeply penetrate the abdominal wall. The use of multiple hooks to distribute the weight of the pannus also reduced pressure and prevented tearing of the skin that can occur when using Steinman pins.…”
Section: Discussionmentioning
confidence: 99%
“…Large body habitus and the presence of a sizeable pannus present an additional challenge for surgeons but also increased risk for patients, as obesity predisposes patients to complications including delayed healing and infection. 5 Despite an associated increased risk, panniculectomies alone have shown to improve patient functionality and QoL, even when considering those who suffered complications such as seroma, infection, or delayed healing. [6][7][8] Previous studies examining concurrent VHR and panniculectomy procedures have reported higher rates of surgical site occurrences (SSOs) than VHRs alone.…”
mentioning
confidence: 99%
“…To address this patient population's needs, concurrent VHR and panniculectomy procedures have been proposed as a method through which to correct abdominal wall defects while simultaneously excising redundant skin and subcutaneous adipose tissue. Large body habitus and the presence of a sizeable pannus present an additional challenge for surgeons but also increased risk for patients, as obesity predisposes patients to complications including delayed healing and infection 5 …”
mentioning
confidence: 99%